Analysis of Pregnancy, Labor and Perinatal Outcomes of Women with Hepatitis C - A. N. Rymashevsky; A. E. Volkov; L. A. Terekhina; E. A. Kovaleva; G. A. Uelina (Медицинский вестник Юга России, 2011)
Purpose: Estimate the influence of infection with hepatitis C virus (HCV) on pregnancy, childbirth and neonatal status.Materials and Methods: Examined 49 pregnant women with HCV (core group). Comparison group consisted of 124 apparently healthy women with physiological pregnancy. In the groups evaluated parity, clinical and laboratory parameters of blood (blood count, hematocrit, leukocyte index of intoxication), during pregnancy, birth, state of newborn babies and their incidence.Results: Pregnancy with HCV occurs with a high incidence of placental insufficiency (almost 2 times more frequently than in the control group, p < 0,05). Effect of HCV on the course of childbirth is not revealed: progress of labor in most cases the same way as in the comparison group. However, in almost equal amounts of blood loss in groups the frequency of postpartum anemia in parturients infected with HCV, we observed significantly more frequently (p < 0,05). The structure of perinatal pathology in infants of women infected with HCV, represented mainly by slowing growth and fetal malnutrition and disorders related to shortening the duration of pregnancy and low birth weight.Summary: HCV is a factor influencing the course of pregnancy, but does not affect the development of perinatal pathology in infants.